Effects of dietary Silybum marianum powder on growth performance, egg and carcass characteristics, immune response, intestinal microbial population, haemato-biochemical parameters and sensory meat quality of laying quails - Rivas Caceres, Raymundo Rene (2024)
The study aimed to assess the effects of different dietary Silybum marianum (SM, milk thistle) powder levels on growth performance, productivity, immunity, small intestine, haemato biochemical parameters, meat quality, and egg and carcass characteristics of laying quails. The experimental subjects consisted of one hundred and eight 43-day-old quails divided into 3 treatments (0, 0.75, and 1.50% SM) with 4 replicates each. The egg characteristics and growth performance of the quails were evaluated. Quails were euthanized for evaluation of carcasses, microbiota, and sensory characteristics of meat. Blood samples were analyzed for haematology and biochemical profile. Silybum marianum at 0.75% and 1.50% significantly (P < 0.05) increased feed intake, enhanced egg characteristics (number, weight, width, length, volume, weight of egg yolk, and eggshell thickness), jejunum and ileum length, spleen weight, lactobacillus population, sensory characteristics of meat, RBC, hemoglobin, erythrocytic indices, concentration of albumin, globulin and TSH. Silybum marianum at 0.75% and 1.50% decreased (P < 0.05) carcass weight (abdominal fat, heart, neck, and pancreas), feed conversion ratio (FCR) based on eggs produced, percentages of heterophils and lymphocytes, concentration of lactate dehydrogenase, population of coliforms clostridia, and Escherichia coli. Aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, and creatine kinase were not significantly (P > 0.05) altered by 0.75% and 1.50% SM. Silybum marianum at both levels (0.75% and 1.50%) may improve growth, egg characteristics, immune response, intestinal morphology and microbiota, meat quality and erythropoiesis, and also lead to decreased cholesterol in laying quails. Economics can be improved, too. The authors recommend adding 1.0% of SM to quail diet